Soil genesis and landscape evolution in the Parana River Delta - Pereyra, F.X. (2004)
The relationships between landscapes features evolution and soil genesis and distribution are studied. The area is located in southern Entre Rios province (33o00'-33o45'S and 58o30'-59o17'W). The Parana River Delta, has a complex genetic evolution, due to river processes, marine ingressions and aeolian actions. These processes resulted in an unstable landscape, that imprinted its particular features in soils. Nine geomorphic units were recognized: 1) Gualeguay river alluvial plain and terraces, 2) Arroyo Ñancay aluvial plain and terrazes, 3) Minor streams aluvial plains, 4) Gualeguay river delta, 5) Deltaic plain, 6) Beach ridges, 7) Old lagoon and tidal plain, 8) Loessic plain and 9) Dunes. Soils are mainly Entisols, Inceptisols and Mollisols, and a spatial trend is recognized in the Delta Region. Soil evolution is controlled by a) an active morphodynamic, b) soil landscape features that resulted in a dominant aquic regime of soils and c) Late Quaternary climatic fluctuations that resulted in sea level variations. Finally, soil development, soil features and distribution and soil drainage are studied in relation with landscape main features and evolution. © 2004 Asociación Geológica Argentina.